Examining recovery experiences as a mediator between physical activity and study-related stress and well-being during prolonged exam preparation at university - Reschke, Tom; Lobinger, Thomas; Reschke, Katharina (PLOS ONE, 2024)
Prolonged study periods such as preparing for comprehensive exams pose a significant source of chronic stress for university students. According to the Conservation of Resources Theory, the replenishment of resources during leisure time is essential to a successful stress recovery process. This study examined the role of recovery experiences as a mediator of the relationship between physical activity as one specific recovery activity and both study-related stress and well-being. We applied a longitudinal design and approached students on three measurement occasions over seven months. The sample consisted of N = 56 advanced law students enrolled at one large German university who were all in their exam preparation to take their final exams. Students gave self-reports on their respective levels of physical activity (predictor), and recovery experiences (mediator), as well as on their study-related stress and well-being (outcomes). Results showed a negative trend in recovery-related variables and the outcomes as exam preparation progressed. There were mostly small correlations between physical activity and both stress and well-being at each measurement occasion. Recovery experiences partially mediated the relationship between physical activity and the outcomes on some measurement occasions. Our results suggest that the positive effects of recovery experiences related to physical activity become more sustained as exam preparation progresses and have a particularly positive impact on well-being. Future research can build on these findings by further examining recovery as an important means to help students better cope with long-lasting and stressful study periods.
Gesehen am 07.01.2025